2017
DOI: 10.1159/000464422
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenesis of Alzheimer's Disease: An Update

Abstract: Dementia is a chronic or progressive syndrome, characterized by impaired cognitive capacity beyond what could be considered a consequence of normal aging. It affects the memory, thinking process, orientation, comprehension, calculation, learning ability, language, and judgment; although awareness is usually unaffected. Alzheimer's disease (AD) is the most common form of dementia; symptoms include memory loss, difficulty solving problems, disorientation in time and space, among others. The disease was first des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
240
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(266 citation statements)
references
References 103 publications
2
240
0
8
Order By: Relevance
“…In our study, NOR test results showed significant improvement in memory following both resistant and strength exercises in AD animals, which is in line with other similar studies [34, 35]. Based on the cholinergic hypothesis of AD, any reduction in the acetylcholine level is the probable cause of AD [36]. Also, the degeneration of cholinergic neurons in basal forebrain plays a key role in AD-induced memory loss and cognitive impairment [37].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, NOR test results showed significant improvement in memory following both resistant and strength exercises in AD animals, which is in line with other similar studies [34, 35]. Based on the cholinergic hypothesis of AD, any reduction in the acetylcholine level is the probable cause of AD [36]. Also, the degeneration of cholinergic neurons in basal forebrain plays a key role in AD-induced memory loss and cognitive impairment [37].…”
Section: Discussionsupporting
confidence: 91%
“…[1] They are found in AD brains and contain high levels of Cu 2 + and Zn 2 + ions embedded with aggregates of the amyloid-b (Ab)p eptide. [1] They are found in AD brains and contain high levels of Cu 2 + and Zn 2 + ions embedded with aggregates of the amyloid-b (Ab)p eptide.…”
Section: Introductionmentioning
confidence: 99%
“…It reduces tau’s affinity for microtubules, and increases its likelihood to aggregate and fibrillize [309]. This leads to destabilization of microtubules with subsequent axonal transport failure and neurodegeneration, which can be offset or corrected by microtubule-stabilizing drugs [24, 40, 405].…”
Section: Tau Pathologymentioning
confidence: 99%